Pelatihan Pemeliharaan Sistem Distribusi Tenaga Listrik pada Tenaga Kerja Perusahaan Bidang Ketenagalistrikan - Salama Manjang; Ikhlas kitta; Syafaruddin -; Yusran -; Indar C Gunadin; Gassing - (Faculty of Engineering UNHAS, 2019)
This community service activity aims to establish a cooperative relationship between the Department of Electrical Engineering, Hasanuddin University and Electrical Engineering Alumni in South Sulawesi. One of the most important professional skills for Electrical Engineering alumni is in the field of maintaining the distribution of electricity. This ability can help graduates to develop their talents, express themselves in the science of electrical engineering, and one of the skills capital to be ready to compete in the job market. That requires knowledge and work experience from electrical engineering alumni to master the field practically with the knowledge that requires refreshment of work competencies in the field of maintenance of electric power distribution. This activity provides training on maintenance of electric power distribution in the form of maintenance of medium voltage overhead, maintenance of distribution substations, maintenance of low voltage overhead, and maintenance of limiting and measuring devices. The preparatory process for the training begins with coordinating with electrical engineering alumni coordinated by partners who are represented through a business entity namely PT. Rahmat Alam Utama related to the schedule, participants, and materials to be given during the training. The implementation team then made some training modules in the form of softcopy as the main material of the training. The training was held for 1 (one) day, which is August 15, 2019, which was attended by 26 electrical engineering alumni. The results of the evaluation of activities through the questionnaire provided showed that most participants had a high level of interest in maintaining electricity distribution and still wanted to attend training at the next opportunity. In addition, there is also the addition of knowledge and skills of the majority of trainees.